On the relationship between urban form and amenities: A new perspective from Qom (Iran) - Venerandi Alessandro; Zamani Vahid; Porta Sergio (Lodz University of Technology Press, 2023)
Amenities are fundamental for urban life as they promote socio-economic interactions and enhance city dynamics. Previous studies investigated the relationship between metrics of street network centrality and urban amenities. However, they hardly focused on further aspects of the built environment. A further drawback is that relationships were mainly assessed through linear models even though more complex and non-linear relationships plausibly exist. In this work, we, first, comprehensively describe the urban form of our case study, the city of Qom (Iran), through a set of 55 morphometrics computed at the plot level; second, we investigate the relationship between these metrics and density of amenities, through a set of machine learning techniques that handle non-linear behaviours. The best model explains up to 45% of the variance of the density measure, with coverage ratio, plot size, floor area ratio, street canyon width, and betweenness centrality being the top five explanatory factors. While the findings of this work do not have universal value, the methodology can be replicated to explore the same research question in different contexts. It can also be used as an evidence-based tool to inform design choices in urban redevelopment affecting the location of amenities in cities.
Keywords: urban morphology; urban morphometrics; machine learning; amenities; Qom (Iran); morfologia miasta; morfometria miasta; uczenie maszynowe; udogodnienia